Estimate op chilling hours below 7°C in Espirito Santo State, Brazil - Guidoni, Antonio Lourenço; Feitoza, Leandro Roberto; Quezada, Fernando Santibánez; Azevedo, Jorge Mameri de (Pesquisa Agropecuaria Brasileira, 2014)
Linear, quadratic and exponencial regression models were compared to estimate the number of hours with temperature equal or below 7°C. The studied equations were functions of the average and minimum monthly temperatures. The quadratic regression equation was found to be the most adequate. Based on common data as the minimum and average temperature, the number of chilling hours could be estimated in a given area of the State of Espirito Santo without actual data.